Effectiveness of Online Lectures Using Digital Platform During the Pandemi Covid-19 - P. Ayu Suci Lestari; Gunawan Gunawan; Syahriani Yulianci (Indonesian, 2020)
The spread of the COVID-19 outbreak disrupted the education sector. These conditions cause the Indonesian government to directly eliminate all face-to-face education activities, including for lecture activities in Higher Education. Alternative solutions offered are lecture activities that are carried out online by utilizing various digital platforms. This study aims to describe general studies' results related to online lectures' effectiveness by using various digital platforms, especially during the COVID-19 pandemic. This research uses the descriptive content analysis study method with information sources derived from various scientific, national, and international articles, which are then analyzed and drawn conclusions to obtain recommendations as a literature study. The review results show that digital platforms such as Zoom, WhatsApp, Google Classroom, Schoology, and Edmodo have a positive and effective impact in improving the quality of online lectures during the COVID-19 pandemic. Signal constraints that are less stable and wasteful of quotas during online lectures can be circumvented by selecting and combining digital platforms to minimize these obstacles while maintaining quality and reducing online courses' essence.